2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944840
|View full text |Cite
|
Sign up to set email alerts
|

Toward using alpha and theta brain waves to quantify programmer expertise

Abstract: Abstract-Empirical studies of programming language learnability and usability have thus far depended on indirect measures of human cognitive performance, attempting to capture what is at its essence a purely cognitive exercise through various indicators of comprehension, such as the correctness of coding tasks or the time spent working out the meaning of code and producing acceptable solutions. Understanding program comprehension is essential to understanding the inherent complexity of programming languages, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Igor Crk and Timotthy Kluthe [ 53 ] performed a study reporting a binary qualification of a programmer’s expertise through code comprehension using recorded EEG signals from 14 electrodes in 34 participants. By using information of Theta and Alpha bands, the authors could distinguish the expertise with an accuracy from 53% to 63% depending on the task.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Igor Crk and Timotthy Kluthe [ 53 ] performed a study reporting a binary qualification of a programmer’s expertise through code comprehension using recorded EEG signals from 14 electrodes in 34 participants. By using information of Theta and Alpha bands, the authors could distinguish the expertise with an accuracy from 53% to 63% depending on the task.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Further research will be needed in order to clarify and explain these relationships. The rapid development of neuroscience research provides more possibilities to uncover the underlying mechanisms of information processing in the brain during computer programming [8] [9]. Knowledge stored in longterm memory and knowledge used in working-memory have previously been found to be good predictors of computer programming skill acquisition in traditional research [10] [11] [12], which has been confirmed by recent research in neuroscience [13] [14].…”
Section: Introductionmentioning
confidence: 81%
“…Consequently, we chose to measure brain activity using EEG which has been successfully used in previous existing cognitive research [15]. In the field of computer programming, a paucity of research exists studying the relationship of EEGs with respect to the cognition of programming dynamics [8] [9]. Although the possible relationship between the memory and programming skill has been depicted in previous research, the use of EEGs in this research is a relatively novel way to explore programming cognition, supplemented by eye tracking to reveal more about how different cognitive models influence programming dynamics and skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with the Emotiv Headset is that it has limited electrodes with no electrodes in the central lobe (Pz, Cz, Fz) and therefore, it is thought that the system has limited applicability in research. The manufacturer states that the signals from the neighboring electrodes are good enough to perform experiments and researchers have proved the capability of headset in many applications [31]. The subjects were given an open-ended task to depict the real-world setting, which results in complex cognitive processing and analysis strategies.…”
Section: Methodsologymentioning
confidence: 99%